2009
DOI: 10.1021/ol901855b
|View full text |Cite
|
Sign up to set email alerts
|

A Multicomponent Coupling Sequence for Direct Access to Substituted Quinolines

Abstract: A titanium-catalyzed three-component coupling reaction can be used to generate tautomers of N-aryl-1,3-diimines. Simple treatment of these products with acetic acid leads to cyclization forming quinoline derivatives in a one-pot procedure. The primary amines employed can be substituted anilines, aminonaphthalenes, or even heterocyclic amines, which leads to a variety of fused-ring heterocyclic frameworks. The one-pot yields varied from 25-71% for the 18 examples presented in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(13 citation statements)
references
References 26 publications
(17 reference statements)
0
12
0
1
Order By: Relevance
“…55 3-cyclohexenyl-2,5,7-trimethylquino-line ( 7 ), 2,5,7-trimethyl-3-phenylquinoline ( 6 ), 5,7-dimethyl-2, 3-diphenylquinoline ( 12 ), 2-methyl-3-phenyl-6-( N,N -dimethy-lamino)quinoline ( 34 ) were synthesized via the literature procedure. 43 …”
Section: Methodsmentioning
confidence: 99%
“…55 3-cyclohexenyl-2,5,7-trimethylquino-line ( 7 ), 2,5,7-trimethyl-3-phenylquinoline ( 6 ), 5,7-dimethyl-2, 3-diphenylquinoline ( 12 ), 2-methyl-3-phenyl-6-( N,N -dimethy-lamino)quinoline ( 34 ) were synthesized via the literature procedure. 43 …”
Section: Methodsmentioning
confidence: 99%
“…This strategy has been extended to the preparation of the natural product withasomnine (Section 15.4.5). Quinolines and their derivatives have been targeted using hydroamination routes over the past several years [351][352][353][354] and recent developments in the application of gold-catalyzed transformations, in particular, has furthered advances in one-pot and tandem approaches for the synthesis of these fused ring systems. In particular, Che and coworkers [355] showed that Au(I)-carbene complexes (42) can be used for tandem hydroamination-hydroarylation to prepare dihydroquinoline and quinoline products (Scheme 15.116).…”
Section: N-heterocycle Synthesismentioning
confidence: 99%
“…Treating 545 with acetic acid generates quinoline 546. The coupling reaction proceeds well with electron‐rich anilines, aminonaphthalenes, and heterocyclic amines, which subsequently cyclize to afford fused heterocycles 166. Typically the reaction is performed in two steps: the azadiene is formed and then the solvent is removed, acetic acid is added, and the reaction mixture is heated to 150 °C for 24–48 h.…”
Section: Miscellaneous Isonitrile Condensationsmentioning
confidence: 99%